The Digital Twin Technology: A Scoping Review of Characterization and Implementation Through Business IT Perspectives - Hein Ko Ko Htet; Indrianawati Usman; M. Yusak Anshori (UNUSA Press, 2023)
Digital twin is a revolutionizing technology. It involves sophisticated models such as real-time data, history data, simulation, machine learning, sensor updates which can reflect almost every detail of the physical objects, procedures, and services. Digital twin technology would be replicated the physical world into a virtual world in the future. Digital twin technology is considered state-of-the-art, but full implementation has yet to occur due to technical challenges and delays. The researchers have to create all the unique and specialized components of the thing or system and collect and combine a massive amount of diverse data. Since, many researchers and employees from some industries such as architecture, health care and engineering are still not completely understood about the technologies and tools used in digital twin technology. This paper illustrates scoping reviews of the characterization, implementation processes of digital twin in business information technology within 5 years period from 2018 to 2022. Furthermore, Digital Twin current applications in three different territories are also outlined in this paper. The purpose of the paper is to understand systematically about the digital twin technology process in different fields.